2021
DOI: 10.3389/fphar.2021.633353
|View full text |Cite
|
Sign up to set email alerts
|

CircMAP3K11 Contributes to Proliferation, Apoptosis and Migration of Human Periodontal Ligament Stem Cells in Inflammatory Microenvironment by Regulating TLR4 via miR-511 Sponging

Abstract: Growing number of studies regarding the role of circRNAs in the development of various diseases have emerged in recent years, but the role of circRNAs in periodontitis pathogenesis remains obscure. Human periodontal ligament stem cells (hPDLSCs) play a critical role in periodontal remodeling, regeneration and repair processes, and their regenerative capacity could be prohibited in local periodontal inflammatory microenvironment. Herein, we sought to uncover the molecular mechanisms of periodontitis pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…There is an emerging understanding of the potential role of circRNA in periodontitis, and in particular, disease pathogenesis. There have been three studies on their presence in PDL tissues [ 37 , 38 , 39 ] and two studies in gingival tissues [ 40 , 41 ] taken from periodontitis patients ( Table 1 ).…”
Section: Circrna Expression In Periodontal Tissuesmentioning
confidence: 99%
See 4 more Smart Citations
“…There is an emerging understanding of the potential role of circRNA in periodontitis, and in particular, disease pathogenesis. There have been three studies on their presence in PDL tissues [ 37 , 38 , 39 ] and two studies in gingival tissues [ 40 , 41 ] taken from periodontitis patients ( Table 1 ).…”
Section: Circrna Expression In Periodontal Tissuesmentioning
confidence: 99%
“…A very recent study by Yu et al [ 37 ] demonstrated that circMAP3K11 (also named hsa_circ_002284) was significantly increased in inflamed PDL tissues from periodontitis ( n = 20), as compared to healthy PDL tissues ( n = 10), using RT-qPCR. Periodontitis patients were selected based on the following criteria—(1) redness and swelling of the gingiva or bleeding on probing; (2) probing depth > 3 mm and attachment loss > 1 mm; and (3) radiographic evidence of horizontal or vertical resorption of alveolar bone.…”
Section: Circrna Expression In Periodontal Tissuesmentioning
confidence: 99%
See 3 more Smart Citations